2015
DOI: 10.1016/j.nefro.2015.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Uso del sevelamer en la enfermedad renal crónica. Más allá del control del fósforo

Abstract: Sevelamer is a non-calcium phosphate binder used in advanced chronic kidney disease (CKD) and in dialysis for hyperphosphataemia control. Several experimental, observational studies and clinical trials have shown that sevelamer has pleiotropic effects, beyond hyperphosphataemia control, including actions on inflammation, oxidative stress, lipid profile and atherogenesis, vascular calcification, endothelial dysfunction and the reduction of several uremic toxins. This is the biological basis for its global effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…In patients with ESKD, use of non-calcium-based phosphate binding agent sevelamer reduced serum cholesterol and markers of inflammation (70). Additionally, sevelamer has shown to be effective in slowing down CAC progression and EF in dialysis patients (46).…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…In patients with ESKD, use of non-calcium-based phosphate binding agent sevelamer reduced serum cholesterol and markers of inflammation (70). Additionally, sevelamer has shown to be effective in slowing down CAC progression and EF in dialysis patients (46).…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…The effects of sevelamer also include actions on oxidative stress, inflammation, lipid profile, endothelial dysfunction, and vascular calcification have been reported. [ 16 ]…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that sevelamer reduces systemic inflammatory response both in an animal model of CKD and in hemodialysis (HD) patients [18, 19]. Other studies have also demonstrated that sevelamer may decrease systemic inflammation in patients with CKD, as it reduces circulating levels of uremic toxins such as AGEs [20] as well as indoxyl sulfate, and p -cresol [17, 21]. Moreover, sevelamer can reduce the expression of adhesion molecules intercellular adhesion molecule-1 (ICAM-1) and VCAM-1 (markers of vascular injury) consequently it reduces circulating and cellular levels of AGEs, increases antioxidant defense, and decreases circulating levels of pro-oxidants molecules [22–24].…”
Section: Introductionmentioning
confidence: 99%